2008
DOI: 10.1097/sla.0b013e31817b6609
|View full text |Cite
|
Sign up to set email alerts
|

Results of Pancreaticoduodenectomy in Patients With Periampullary Adenocarcinoma

Abstract: Perineural growth is a more important risk factor for survival than the primary site of periampullary carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(18 citation statements)
references
References 51 publications
2
15
1
Order By: Relevance
“…Diverging from other papers, in which perineural invasion was strictly correlated with poorer overall long-term survival 5 , 27 , in this study, this feature was not associated with better or worse prognosis.…”
Section: Discussioncontrasting
confidence: 47%
“…Diverging from other papers, in which perineural invasion was strictly correlated with poorer overall long-term survival 5 , 27 , in this study, this feature was not associated with better or worse prognosis.…”
Section: Discussioncontrasting
confidence: 47%
“…Major determinants of survival are tumor characteristics[35], and the presence of disseminated disease[36]. Other factors like psycho-social and bio-behavioral influences[37], environmental influences, and income-related lifestyle factors may play a role in cancer pathogenesis[5,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding median survival times were 15.0 months (pancreatic head), 31.9 months (ampulla of Vater), 102.0 months (distal bile duct), and 44.4 months (duodenum). [42] Pancreatic malignancies overall are associated with poor long-term prognosis. Five-year survival rates following pancreatic resection for pancreatic adenocarcinoma remain low (<20%), even in large volume institutions.…”
Section: Discussionmentioning
confidence: 99%
“…This result is also in line with previously published results for periampullary carcinomas, including a recently published series from Birmingham which reported an actuarial five year survival of 60% for ampullary carcinoma following resection. [44] An involved pancreatic resection margin is associated with poor patient outcome. [45] A recent study reported a margin of ≥1.5 mm to be associated with better outcome.…”
Section: Discussionmentioning
confidence: 99%